2016
DOI: 10.5194/bg-2016-52
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial dynamics in a High-Arctic glacier forefield: a combined field, laboratory, and modelling approach

Abstract: <p><strong>Abstract.</strong> Modelling the development of soils in glacier forefields is necessary in order to assess how microbial and geochemical processes interact and shape soil development in response to glacier retreat. Furthermore, such models can help us predict microbial growth and the fate of Arctic soils in an increasingly ice-free future. Here, for the first time, we combined field sampling with laboratory analyses and numerical modelling to investigate mi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 71 publications
(126 reference statements)
2
26
1
Order By: Relevance
“…In contrast to model simulations by Bradley and others (2016) which showed that inorganic N accumulates at a relatively constant rate within Midtre Lovénbreen forefield, we observed that concentrations of inorganic N remain largely stable at 3–4 µg g −1 between the 0- and 113-year-old soils (Figs 3b and c). As NO 3 -N was found to constitute 100% of inorganic N in the silt loam-textured soils (ice-free for 0–50 years), it may be reasoned that inputs of NH 4 -N are rapidly immobilised by the soil microbial biomass (Bradley and others, 2016). Indeed, a study of the Loch Vale Watershed in the Colorado Rocky Mountains, USA, by Baron and others (1995) showed that NH 4 -N, which comprised ~50% of received inorganic N deposition, was incorporated directly into biomass or oxidised to NO 3 -N in soil, as well as snow pack and surface waters.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to model simulations by Bradley and others (2016) which showed that inorganic N accumulates at a relatively constant rate within Midtre Lovénbreen forefield, we observed that concentrations of inorganic N remain largely stable at 3–4 µg g −1 between the 0- and 113-year-old soils (Figs 3b and c). As NO 3 -N was found to constitute 100% of inorganic N in the silt loam-textured soils (ice-free for 0–50 years), it may be reasoned that inputs of NH 4 -N are rapidly immobilised by the soil microbial biomass (Bradley and others, 2016). Indeed, a study of the Loch Vale Watershed in the Colorado Rocky Mountains, USA, by Baron and others (1995) showed that NH 4 -N, which comprised ~50% of received inorganic N deposition, was incorporated directly into biomass or oxidised to NO 3 -N in soil, as well as snow pack and surface waters.…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, the increase in NH 4 -N in the 113- and 2000-year-old soils (Fig. 3b) suggests that mineralisation processes are sufficient to facilitate the accumulation of inorganic N in the clay-textured soils (Bradley and others, 2016). This is supported by studies of the Damma glacier (Switzerland; Töwe and others, 2010), and Ödenwinkelkees and Rotmoosferner glaciers (Austria; Tscherko and others, 2003) which showed that functional genes ( chiA and aprA ) and rates of N mineralisation increase with soil age, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The clear separation of early bacterial succession from transitional and late stages could be due to various reasons. Such as the early stage soil was exactly collected from the glacier tongue, and that the bacterial community could be derived from subglacial and/or glacial environment as observed by a previous study (Bradley et al, 2016). While the discrimination in the transitional and late stages for more or less could be due to soil physicochemical factors and among microbial interaction.…”
Section: Discussionmentioning
confidence: 99%
“…A clear change in runoff amplitudes after 28th July 2012 coincided with the supraglacial catchment losing most of its snow cover, exposing supraglacial stores of OC. Future studies should test this hypothesis because this will impact estimates of OC release from glaciers with consequences for downstream extraglacial ecosystems (Fellman et al ., ; Hood et al ., ; Bradley et al ., ).…”
Section: Discussionmentioning
confidence: 99%